2013
DOI: 10.1111/liv.12047
|View full text |Cite
|
Sign up to set email alerts
|

Increased renal expression and urinary excretion of TLR4 in acute kidney injury associated with cirrhosis

Abstract: The data provide proof of concept that renal dysfunction in patients with cirrhosis with superimposed inflammation is associated with significant tubular injury and apoptosis and with increased renal expression and urinary excretion of the TLR4, suggesting a potential role of TLR4 as mediator of renal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 33 publications
(51 reference statements)
2
72
0
4
Order By: Relevance
“…Renal dysfunction in patients with cirrhosis with superimposed inflammation was reported previously to be associated with significant tubular injury (Shah et al, 2013). This model also showed elevated oxidative stress in the present study, represented by the increased MDA and the reduced total antioxidant which might be a biomarker of tissue destruction and inflammation in both kidney and liver.…”
Section: Discussionsupporting
confidence: 65%
“…Renal dysfunction in patients with cirrhosis with superimposed inflammation was reported previously to be associated with significant tubular injury (Shah et al, 2013). This model also showed elevated oxidative stress in the present study, represented by the increased MDA and the reduced total antioxidant which might be a biomarker of tissue destruction and inflammation in both kidney and liver.…”
Section: Discussionsupporting
confidence: 65%
“…Putting these observations together, like a jigsaw puzzle, the missing piece becomes the following: can a more severe degree of inflammation and/or lesser tolerance to it affect the development of a type of kidney damage other than that of HRS? It has been observed in clinical [17] as well as in experimental studies [18] that in cirrhosis and superimposed infection/inflammation, an up-regulation of renal tubular TLR4 may occur, associated with the development of florid renal dysfunction with tubular damage and apoptosis. Renal dysfunction in these patients is associated with significant tubular injury and apoptosis and with increased renal expression and urinary excretion of the TLR4, suggesting a potential role of TLR4 as mediator of renal injury [17].…”
Section: Pathogenesis Of Sepsis Induced-akimentioning
confidence: 98%
“…It has been observed in clinical [17] as well as in experimental studies [18] that in cirrhosis and superimposed infection/inflammation, an up-regulation of renal tubular TLR4 may occur, associated with the development of florid renal dysfunction with tubular damage and apoptosis. Renal dysfunction in these patients is associated with significant tubular injury and apoptosis and with increased renal expression and urinary excretion of the TLR4, suggesting a potential role of TLR4 as mediator of renal injury [17]. Although the mechanism of up regulation of tubular TLR4 is not entirely clear, it seems likely to be a consequence of the continuous exposure to gut bacterial translocation [17] and may be prevented by gut decontamination with norfloxacin [18].…”
Section: Pathogenesis Of Sepsis Induced-akimentioning
confidence: 98%
“…Kim-1 is a member of the immunoglobulin family and is expressed in the surface of activated T cells (CD4 + Th2) (32); therefore, sKim-1 may be involved in the immune response to sepsis and its level is higher than normal in this condition. Previous animal and clinical studies have demonstrated (33,34) that Kim-1 is an inflammation mediator associated with the pathogenesis of asthma and rheumatoid arthritis. A prospective, multicenter cohort study (35) found that Kim-1 peaked at 2 days after cardiac surgery in adults and at 1 day after surgery in children, and that the elevations of Kim-1 were associated with AKI and adverse outcomes in adults.…”
Section: Group a (N=17) Group B (N=21) ------------------------------mentioning
confidence: 99%